Life finds a way : what evolution teaches us about creativity - Wagner, Andreas, 1967 January 26- (Basic Books, 2019)
In Life Finds a Way, biologist Andreas Wagner reveals the deep symmetry between innovation in biological evolution and human cultural creativity. Rarely is either a linear climb to perfection--instead, "progress" is typically marked by a sequence of peaks, plateaus, and pitfalls. For instance, in Picasso's forty-some iterations of Guernica, we see the same combination of small steps, incessant reshuffling, and large, almost reckless, leaps that characterize the way evolution transformed a dinosaur's grasping claw into a condor's soaring wing. By understanding these principles, we can also better realize our own creative potential to find new solutions to adversity. Ultimately, Life Finds a Way offers a new framework for the nature of creativity, enabling us to better adapt, grow, and change in art, business, or science--that is, in life.